Genetic Diversity Analysis In Brassica rapa Using Morphological Characters (Bangladesh Journal of Agricultural Research, 2013)
A field experiment was conducted in the experimental field of Genetics and Plant Breeding Department, Sher-e Bangla Agricultural University, Dhaka, Bangladesh to study on genetic diversity in 10 F4 lines obtained through intervarietal crosses along with 8 released varieties of Brassica rapa during November 2007 to February 2008. Different Multivariate analyses were performed to classify 18 genotypes. All the genotypes were grouped into four clusters. Cluster IV was the largest comprising of 7 genotypes and cluster II was the smallest with 2 genotypes. Cluster II had the highest intra-cluster distance and Cluster I had the lowest intra cluster distance. Inter cluster distance was maximum (11.697) between clusters II and III. The results revealed that genotypes chosen for hybridization from clusters with highest distances would give high heterotic F1 and broad spectrum of variability in segregating generations. The characters- number of primary branches/plant, number of secondary branches/plant and days to 50% flowering contributed maximum towards divergence among Brassica genotypes. Considering cluster distance, inter genotypic distance and other agronomic performance G2 and G14 from cluster I; G18 from cluster II; G1, G9 and G12 from cluster III and G16 and G17 from cluster IV may be considered as better parents for future uses in hybridization program. Bangladesh J. Agril. Res. 38(1): 11-18, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15185